Designing Live2D Character Illustrations To Increase Engagement On CV. Pustaka Cemerlang's Instagram - Symonsz, Domenique Issabell Nhatassa; Setiawan, Bayu; Yani, Aditya Rahman (Gondang: Jurnal Seni dan Budaya, 2025)
Social media platforms like Instagram have become crucial tools for promoting products and services, including in children's education. CV. Increasing audience engagement on social media, especially through interesting content, is challenging for Pustaka Cemerlang. A solution to produce more dynamic and interactive content that engages viewers, particularly young ones, is to use animated characters, particularly those that use Live2D technology. This study uses a qualitative descriptive approach to investigate audience preferences for animation and character design through questionnaires, observations, and interviews. Simple, happy, and instantly identifiable characters are excellent at promoting children's learning and increasing audience engagement with the company's material. This study explores how Live2D character design can enhance visual appeal and engagement with viewers on the Instagram platform of CV. Pustaka Cemerlang.